A comparison of gender diversity in transgender young people with and without autistic traits from the Trans 20 cohort studyResearch in context - Michelle A. Tollit; Tiba Maloof; Monsurul Hoq; Kristina Haebich; Carmen C. Pace; Zamantha Munoz Rodriguez; Muhammad Sial; Jonathan M. Payne; Ken Pang (Elsevier, 2024)
Summary: Background: There is an elevated co-occurrence of autism in trans individuals, with recent meta-analyses suggesting that 11% of trans individuals are autistic. The presence of autism in trans young people can create clinical challenges by adding complexity to the presentation, assessment and management of those presenting to gender clinics. Although many trans young people display traits of autism, how these traits relate to the nature of their gender diversity is unclear. Methods: This study compared gender identity, gender expression and gender dysphoria (GD) in trans young people with and without autistic traits. Baseline data from a cohort study of trans children and adolescents who first attended the Royal Children's Hospital Gender Service (Victoria, Australia) between February 2017 and January 2020 were analysed cross-sectionally. Autistic traits were assessed via the Social Responsiveness Scale-2. Gender was assessed using tools that measure gender identity, social transition, GD, body dissatisfaction, voice dysphoria, and chest dysphoria. Findings: 522 participants were included, of whom 239 (45.8%) exhibited autistic traits (SRS total T-score ≥60). Those with and without autistic traits were similar in their age (mean (SD) age 14.0 (2.9) and 13.1 (3.6) years respectively) and gender identity: the majority (73.7% (n = 174) and 70.5% (n = 198) respectively) identified in a binary way. Higher rates of social transition (specifically, changing pronouns) were noted in those with autistic traits (Difference in proportion 11.7, 95% confidence interval [CI] 2.4-21.1, p = 0.014). GD was high in both groups with ∼95% displaying clinically relevant levels of GD. Chest dysphoria was similar between groups, while voice dysphoria was higher in those with autistic traits (standardised mean difference [SMD] = 0.3, 95% confidence interval [CI]: 0.1-0.5 p = 0.00087). Dissatisfaction with secondary gendered characteristics (SMD = 0.3, CI: 0.1-0.5 p = 0.0011) and hormonally unresponsive body characteristics (SMD = 0.2, CI: 0.1-0.4 p = 0.016) was higher in trans young people with autistic traits. Interpretation: The similarly high severity of GD in those with and without autistic traits reinforces the importance of trans young people with and without autistic traits being availed the same opportunities to access gender-affirming care. Subtle differences identified between the groups in other areas of gender diversity suggest trans young people with autistic traits may have distinct needs and that gender-affirming care may need to be tailored accordingly. Funding: The Royal Children's Hospital Foundation, Hugh D.T. Williamson Foundation; Australian National Health and Medical Research Council-Clinical Trials and Cohort Studies scheme (GNT 2006529).